2016
DOI: 10.1155/2016/1712383
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence Properties of Novel Self-Agglomerating CaSO4:Eu Phosphors Obtained by an Environmentally Friendly Method

Abstract: In this work, we report the thermoluminescence (TL) properties of self-agglomerating CaSO4:Eu samples obtained by an environmentally friendly coprecipitation technique. No binding material is needed to form solid CaSO4:Eu samples. Samples exposed to beta particle irradiation exhibit a TL maximum at 473.15 K when a 5 K/s heating rate is used, they are two times more sensitive than the TLD-100 commercial dosimeter, and their lower detection limit was determined to be less than 0.69 mGy. The computerized glow cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…When comparing CaSO 4 :Eu with the previously prepared TL compositions of CaSO 4 , it was found that CaSO 4 :Eu was twice as sensitive as TLD‐100 and had a lower detection level of 0.69 mGy. In contrast, the current composition exhibited lower sensitivity, ~0.9 times less sensitive, and a higher detection level of 8.57 mGy [29, 30]. The prepared phosphor has an MDD that was in line with that of the CaSO 4 :Tb,Eu phosphor, which had an MDD of 4.72 mGy [13].…”
Section: Resultsmentioning
confidence: 97%
“…When comparing CaSO 4 :Eu with the previously prepared TL compositions of CaSO 4 , it was found that CaSO 4 :Eu was twice as sensitive as TLD‐100 and had a lower detection level of 0.69 mGy. In contrast, the current composition exhibited lower sensitivity, ~0.9 times less sensitive, and a higher detection level of 8.57 mGy [29, 30]. The prepared phosphor has an MDD that was in line with that of the CaSO 4 :Tb,Eu phosphor, which had an MDD of 4.72 mGy [13].…”
Section: Resultsmentioning
confidence: 97%